2009
DOI: 10.1590/s0104-56872009000400009
|View full text |Cite
|
Sign up to set email alerts
|

Correlação entre métodos de aleitamento, hábitos de sucção e comportamentos orofaciais

Abstract: Background: the development of oral motor control depends partially on motor and sensory experiences. Aim: to analyze the relationship between the duration of breastfeeding, artificial feeding and sucking habits, and of these parameters with the orofacial motor performance. Method: participants of this study were one hundred and seventy-six children aged 6 to 12 years. All subjects were submitted to an orofacial myofunctional clinical examination, using a protocol with scores, and parents/care takers were inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
18
1
17

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 17 publications
(19 reference statements)
4
18
1
17
Order By: Relevance
“…The unmet psycho-emotional needs due to inadequate time for breastfeeding and the introduction and extended use of bottles, may lead the child to meet those needs using devices such as pacifiers or their own thumb 3,22 . Several studies found a relationship between the presence of habits and early weaning, as well as the continuation of artificial feeding 17,23,24 , which is in agreement with the results of this study.…”
supporting
confidence: 93%
See 1 more Smart Citation
“…The unmet psycho-emotional needs due to inadequate time for breastfeeding and the introduction and extended use of bottles, may lead the child to meet those needs using devices such as pacifiers or their own thumb 3,22 . Several studies found a relationship between the presence of habits and early weaning, as well as the continuation of artificial feeding 17,23,24 , which is in agreement with the results of this study.…”
supporting
confidence: 93%
“…Besides that, it benefits the correct positioning of the tongue, through the adapting of tonicity due to its intense muscular activity 2,15 . When the bottle is introduced and its use remains for a long period, this movement is impaired, interfering with the development of orofacial functions and structures 16,17 . Moreover, the introduction of bottles may stimulate the emergence of other deleterious oral habits, since the child does not meet his/her needs of sucking and eventually acquires non-nutritive sucking habits, such as the pacifier or finger sucking 2,3,6 .…”
Section: Methodsmentioning
confidence: 99%
“…In João Pessoa city, children with less breastfeeding duration, developed deleterious oral habits more frequently, with a risk seven times greater than those breastfed for a minimum period of six months 8 . A negative relation of between breastfeeding duration and prolonged sucking habits was found in a study conducted in Ribeirão Preto city, São Paulo state 17 . Most observational studies describe Maternity leave allows mothers to take care of their children more thoroughly, what can contribute to exclusive breastfeeding until six months of age.…”
Section: Discussionmentioning
confidence: 91%
“…Children with shorter breastfeeding time more often developed harmful oral habits with relative risk 7 times greater compared to breastfeeding of at least six months [24].…”
Section: Discussionmentioning
confidence: 99%